Factors Influencing Compliance With Pulmonary Tb Patients At The Lampaseh Health Center, Banda Aceh City Year 2021 - Yani Lestari; Aspiati Aspiati (Sean Institute, 2021)
Pulmonary Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis and is a health problem at the Lampaseh Health Center in Banda Aceh City in 2021. To achieve recovery, it is necessary to adhere to medication for every patient with pulmonary TB and this compliance is influenced by many factors. The purpose of this study was to find out the factors that influence medication adherence of pulmonary TB patients at the Lampaseh Health Center in Banda Aceh City in 2021, with a cross-sectional research design by knowing the factors that influence medication adherence of pulmonary TB patients at the Lampaseh City Health Center Banda Aceh 2021 which will be held in September 2020 - January 2021. The population in this study were 124 pulmonary TB patients. The sampling technique used was Accidental Sampling, namely patients who came to the Health Center to take drugs regularly with a sample size of 25 people. From the results of the study it was found that the factors that influence adherence to taking medication in pulmonary TB patients areknowledge (96%), motivation (100%), attitude (100%), physical ability (92%), family support (96%), counseling (100%) and side effects (68%). From the results of this study it can be concluded that knowledge, motivation, attitudes, physical abilities, family support, counseling and side effects affect medication adherence in pulmonary TB patients. Therefore, researchers suggest that it is necessary to carry out counseling by health workers and family supervision of pulmonary TB patients so that treatment does not fail and recovery can be achieved.